Analisis Kinerja Keuangan Menggunakan Metode Du Pont Di CV. Subur Lestari Jaya Bersama Kota Lubukinggau - Yuli Efrianti; Fitria Fitria (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
The problem in this research is the fluctuation in the amount of net sales, total assets, and net income. That is, this also affects the company's financial performance. To find out the company's financial performance, it can be calculated using financial ratios. The research method used is a qualitative research method using quantitative data through primary and secondary sources. The data collection techniques used were observation, documentation and interview data collection techniques. Based on research using Return On Asset, Total Asset Turnover, and Net Profit Margin in measuring financial performance at CV. Subur Lestasi Jaya Bersama Lubuklinggau, the results of this study indicate that the value of Return On Assets has fluctuated or fluctuated over the last five years, from 2014-2018. The value of Total Asset Turnover is in the very good category, with the lowest decline in 2018, the highest value in 2017. Net Profit Margin has fluctuated or fluctuated during the last five years, namely 2014-2018. This means that this company has not been effective in terms of financial performance, seen from the fluctuating value during the five periods of ROA. Keywords: Financial performance, Return On Asset, Total Asset Turnover, and Net Profit Margin